Paradigma Baru Ekonomi Keluarga dalam Pembangunan Hukum Ekonomi untuk Mewujudkan Ketahanan Nasional - Buswin Wiryawan (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2023)
Purpose: To find out the role of the government in providing wider space to regulate the economy in order to achieve people's welfare, where the people are the goal of national economic development. Method: This study was compiled using a normative juridical approach, in which the author conducted research by examining legal principles and theories, along with the provisions in statutory regulations and legal literature. Result: The concept of the family economy is in line with the provisions of Chapter XIV concerning the National Economy and Social Welfare Article 33 of the 1945 Constitution. Based on these provisions, it can be said that Indonesia does not adhere to a capitalist economic system or a planned economic system or an Islamic economic system but tries to accommodate various economic systems with an emphasis on in a planned economic system. Contribution: This context is expected to be able to face and overcome all threats, challenges, obstacles, and disturbances to the continuity of the national economy.